Apakah Interaksi Otoritas Pajak Dengan Wajib Pajak Meningkatkan Kepatuhan? - Rahmat Safarudin; Dhian Adhetiya Safitra (Universitas Katolik Soegijapranata, Semarang, 2023)
The interaction between the Tax Authorities and Taxpayers through written communications with enforcement letters, soft letters and direct communications through visits was expected to increase tax compliance. This study aims to determine the effect of the interaction between the tax authorities and taxpayers on taxpayer compliance. The analysis of this research used non-employee individual taxpayers registered as taxpayers at KPP Pratama Klaten. Data were analyzed using probit regression. The results of this study indicated that the interaction with a soft letter (SP2DK) and an enforcement letter had a significant negative effect on compliance, while the interaction with visits had a significant positive effect on formal compliance. Based on the results of this study, it is hoped that the Tax Authorities in Indonesia will consider to make more effective policies and strategies related to interactions with taxpayers.